The impact of macroeconomic factors on the financial performance of the food and beverage industry – evidence from Vietnam - Hoi, Chung Tan (Edelweiss Applied Science and Technology, 2025)
This study evaluated the impact of inflation, economic growth (GDP), and interest rates on the financial performance of food and beverage (F&B) companies in Vietnam between 2015 and 2024. We used panel data from the financial reports of 28 F&B companies listed on the Vietnamese stock exchange. This was combined with macroeconomic data from the World Bank, the State Bank of Vietnam, and the General Statistics Office of Vietnam. The econometric model was estimated using the Feasible Generalized Least Squares (FGLS) method to address issues of heteroskedasticity and autocorrelation. The results indicate that inflation has no significant impact on financial performance, owing to Vietnam’s stable inflation rate. GDP growth positively affects financial performance, while interest rates have a negative impact. Firm size positively influences performance, whereas capital structure and capital expenditure are insignificant. These findings provide a basis for F&B enterprises to optimize financial strategies, particularly in high-interest-rate environments, and support policies to maintain stable GDP growth. This study is among the first in Vietnam to use long-term data and the FGLS model to analyze the impact of macroeconomic factors on the financial performance of the F&B industry.